KONSEP PLURALISME DALAM TASAWUF FALSAFI - Muhaemin Latif; Daud, Amiril Mueminin; Muhammad Amri (Living Islam: Journal of Islamic Discourses, 2023)
Uniting Allah swt is one of the obligatory foundations in Islam. Therefore, Islamic scholars flocked to look for a valid concept of the oneness of Allah when faced with the plurality of things that can be sensed by humans, be it the sun, moon, mountains, trees, animals, to the plurality of humans themselves. As one of the colors of Islam, Sufism was also present to develop the concept of monotheism. Which is filled with debates between the pros and cons to this day. His understanding that looks eccentric/anti-mainstream is often in the spotlight. So that not a few Sufi figures were excommunicated, imprisoned, tortured and killed. Concepts such as fana', baqa', ittihad, Hulul, Wihdat al-Manifest, Nur Muhammad to the limits of the Ahlu Sunnah wal Jama'ah madhhab in Sufism are intellectual and cultural properties that were inherited by the previous Sufis to the generations of Islam after them. Therefore, this research is a library research, which tries to answer questions about the Sufism concept of the plurality of beings and the oneness of The Creator.